Play and Graded Exposure Psychotherapies on School Refusal Behaviour amongLower Basic Pupils in Public Schools in Ogun State, Nigeria - Abiola Oluwayemisi Ajani; Moses Oluwafemi Ogundokun (Educational Psychology Journal, 2025)
This study examined the effects of Play Therapy (PT) and Graded Exposure Therapy (GET) on School Refusal Behaviour (SRB) among Lower Basic Pupils (LBP) in public schools in Ogun State, Nigeria. The moderating effects of gender and Academic Self-efficacy (ASE) was also examined. A pretest-posttest, control group quasi-experimental design with a 3x2x3 factorial matrix was adopted. The multistage sampling procedure was used. Three Local Government Areas were randomly selected. Three schools (one per Local Government Area) were randomly selected and assigned to treatment and control groups. The pupils were screened with the School Avoidance Scale (α=.76) and School Attendance Register. 45 pupils who scored above 30.0% were assigned to PP (16), GET (15) and Control (14) groups. The instruments used were School Refusal Assessment (α=.75) and ASE (α=.87) scales. The intervention lasted eight weeks. Analysis of Covariance and Bonferroni post hoc test were used to analyse data at 0.05 level of significance. There was a significant main effect of treatment on SRB among the pupils (F(2; 28)=91.10; partial ῆ2=0.87). The participants in control group had the highest post mean score (80.56), followed by GET (39.65) and PT (36.15). This implies that the PT reduced SRB most among LBP followed by GET. There were no significant interaction main effects of treatments and gender, treatments as well as gender and ASE on SRB. The three-way interaction effect was also not significant. PT and GET were effective in reducing SRB among LBP in Ogun State, Nigeria, irrespective of their gender and academic self-efficacy. Counselling and educational psychologists should make use of this intervention when dealing with such pupils.